2019
DOI: 10.2478/foecol-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dormancy-breaking methods on germination of the water-impermeable seeds of Gleditsia caspica (Fabaceae) and seedling growth

Abstract: Various treatments can be used to break physical dormancy (PY, i.e. water-impermeable seed coat) of legume species, but the effects of these treatments on seedling growth are of great importance in the success of afforestation projects. Our aims were to determine the effects of 20 PY-breaking treatments on (1) germination of Gleditsia caspica (Caspian locust) seeds and (2) seedling growth. Five germination and nine seedling growth and morphological traits were studied. Immersion in concentrated sulfuric acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For dry mass of whole seedlings, length of the largest root, and shoot length, exponential increases occurred up to 55.00, 37.63, and 44.44 min, respectively (Figure 2). The effects of seed immersion times in sulfuric acid on seedling development and initial growth have been reported for several species (Silva et al, 2018;Nourmohammadi et al, 2019). Nevertheless, the results found in literature are generally contrasting and inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…For dry mass of whole seedlings, length of the largest root, and shoot length, exponential increases occurred up to 55.00, 37.63, and 44.44 min, respectively (Figure 2). The effects of seed immersion times in sulfuric acid on seedling development and initial growth have been reported for several species (Silva et al, 2018;Nourmohammadi et al, 2019). Nevertheless, the results found in literature are generally contrasting and inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in previous experiments with the related species C. varia, GA 3 , sulfuric acid, and HCl were tested. The best results were obtained using GA 3 , contrary to other Fabaceae species, where mechanical abrasion or sulfuric acid improves germination [19,20]. With this information, an experiment to compare different concentrations of GA 3 was set.…”
Section: Gibberellin Treatments For Seed Germinationmentioning
confidence: 99%
“…On husk media, the development the emergence of the first folium compositum was seen on day 20 (12 leaves), the second compound leaf on day 30 (30 leaves), the third compound leaf on day 40, and the fourth compound leaf on day 50 (20 leaves) (Figure 3). Based on study about effect of dormancy-breaking methods on germination of Gleditsia capsica (Fabaceae), revealed that the largest number of leaves per seedlings was derived from seeds treated for different periods time with sulfuric acid for 60 and 120 minutes (14).…”
Section: Cotyledons Emergedmentioning
confidence: 99%